The Evaluation Model of Garbage Classification System Based on AHP - Jiangpeng Li; Kui Shi; Zhiqiang Zhou; Hui Xu (International Journal of Engineering and Management Research, 2020)
Based on Shenzhen as an example, the questionnaire was designed in advance to get statistical data. In this paper, the AHP and the linear weighted sum method are used for the weight calculation of each factor, obtaining the long-term cost benefit function of the garbage classification system and the garbage classification pattern grading. Finally, we can choose the better garbage classification mode according to this score.